IEEE GLOBECOM 2008 - 2008 IEEE Global Telecommunications Conference 2008
DOI: 10.1109/glocom.2008.ecp.119
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Handoff between 802.11 and 802.16 Wireless Access Networks

Abstract: Heterogeneous wireless networks will be dominant in the next-generation wireless networks with the integration of various wireless access networks. Wireless mesh networks will become to a key technology as an economically viable solution for wide deployment of high speed, scalable and ubiquitous wireless Internet services.In this thesis, we consider an interworking architecture of wireless mesh backbone and propose an effective vertical handoff scheme between 802.11 and 802.16 wireless access networks. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
0
11
0
4
Order By: Relevance
“…From the related works, we found that mostly the two works are related to our work which are [15] and [16]. Both papers developed the schemes for the seamless vertical handover between the 802.16 and the 802.11.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the related works, we found that mostly the two works are related to our work which are [15] and [16]. Both papers developed the schemes for the seamless vertical handover between the 802.16 and the 802.11.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…An inter-working architecture of wireless mesh backbone and vertical handoff scheme between the 802.11 and the 802.16 is presented in [15]. The handoff signaling procedure in different scenarios has been discussed with the aim to reduce the signaling overhead on the backbone and to provide a lower handoff delay based on the call admission control (CAC).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…MIH mechanism is a very important contribution since it isolats ANS mechanisms from mechanisms to gather information from the networks. In [21], [22] the authors evaluated the performance of a VHO scheme between 802.11 and 802.16 in terms of signaling cost, handover delay, packet loss and QoS. The authors considered an interworking architecture of wireless mesh backbone and proposed a vertical handoff scheme between 802.11 and 802.16 wireless access networks.…”
Section: Related Workmentioning
confidence: 99%
“…In [4] the handover latency for the cases where UDP and TCP carry 2 Journal of Computer Systems, Networks, and Communications MIH signaling messages is compared and some of the design tradeoffs are presented. The evaluation of the performance of a vertical handoff scheme between 802.11 and 802.16 wireless access networks with respect to signaling cost, handoff delay, and QoS support can be found in [5]. Reference [6] evaluates a proposed cross-layer mechanism for making intelligent handover decisions in FMIPv6 in terms of handover latency, packet loss and handover signaling overhead, and [7] evaluates a new enhanced Media Independent Handover Framework (eMIHF) that allows for efficient provisioning and activation of QoS resources in the target radio access technology during the handover preparation phase.…”
Section: Related Workmentioning
confidence: 99%